Glucocorticoid-induced Tumor Necrosis Factor Receptor Negatively Regulates Activation of Human Primary Natural Killer (NK) Cells by Blocking Proliferative Signals and Increasing NK Cell Apoptosis - Liu, Baoying (American Society for Biochemistry and Molecular Biology, 2008)
Glucocorticoid-induced tumor necrosis factor receptor (GITR), found constitutively expressed on human primary natural killer (NK) cells at low levels was up-regulated upon stimulation by either Toll-like receptor ligand or NK cell growth factor, interleukin (IL)-15. cDNA microarray analysis showed that engagement of GITR primarily suppressed the activation of NF-KB pathway of NK cells and up-regulated anti-inflammatory genes heme oxygenase-1 and IL-10. Further analysis revealed that GITR activation suppressed NK cell proliferation in response to IL-15. GITR activation also suppressed proinflammatory cytokine secretion and increased NK cell apoptosis. GITR activation resulted in blocked phosphorylation of Stat5 and Akt, which may have contributed to the observed antiproliferative effect of GITR on NK cells. Increased apoptosis was independent of the Fas-FasL pathway, but Bcl-XL and phospho-Bad protein expressions were diminished, suggesting involvement of the mitochondrial apoptosis pathway. The results suggest that although GITR is an activation marker for NK cells similar to that for T cells, GITR serves as a negative regulator for NK cell activation. Our studies demonstrate a novel physiological role of GITR on NK cells.